THE REPRESENTATION OF MUSLIM AMERICAN IN KARAN JOHAR’S MOVIE MY NAME IS KHAN - PUTRI, SARAH WIDITA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Representation, Muslim American, My Name is Khan. Literature always appear with the story about something that reflects or describes the human life. Movie can be a medium of communication. Movie is one of mass media that deliver some minds, aspiration, and controversial issue. My Name is Khan presents the reflection in United States about how American treat Muslim unfairly where the United States is the country of various religion, ethnics, and uphold the human rights. Directed by Karan Johar, a movie entitled My Name is Khan has a characteristic of moral value which aims to correct misconception about Islam. The misconception about Islam are Islamic fundamental, Al-Qaeda and so on which is not all society knows about it.This movie tried to deliver the meaning and moral value without taking a side, in this case the Muslim. To study this movie, Representation by Stuart Hall is used to help the writer analyzes the data of the study more objectively and accurately, then the mise en scene used to help interprets the meaning from figures of the movie in order to reveal the representation of Muslim American after tragedy 9/11.The result of this study reveal that the representation of Muslim American are represented as the victim of misconception about Islam however despite all the representation, they are represented as tolerance, and religious, and people who praise humanity based on the five pillars and Islam fundamental. Furthermore, Karan Johar gives the representation about Muslim American after 9/11 through Rizwan which is treated unfairly by American and it is proven by a lot of scenes. Nowadays, there are some movies which have similar theme as My Name is Khan. So the writer suggests to the next writer to conduct a study by comparing theme in My Name is Khan with another movie using theory of comparative literature. The theory of comparative literature can be used to reveal how Muslim American is represented through two or more movies which has similar theme.